FUNDAMENTAL ASPECTS AND PRACTICAL PRINCIPLES OF LECTIN SYSTEMS ON THE EXAMPLE OF SYMBIOTIC MICROBIOCENOSIS STRAINS AND CONSORTIA - M. V. Lakhtin (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Prospects of lectin systems of the human biotope symbiotic microorganisms are evaluated. Symbiotic lectins are described as metabolome-biotic imitators of probiotics, carriers, deliveries, depositors, and agents realizing glycoconju-gate metabiotics. Glycoconjugate metabiotics (adequate to symbiotic lectins) represent antagonistic factors against relatively pathogenic microorganisms. Such glycoconjugates include prebiotics, therapeutic agents, décor panels currently supporting normally functioning human cells, tissues and organs. Symbiotic lectins, interacting to synthetic glycoconjugate imitators of important substances for human interactome, serve as instruments for screening strains and their consortia possessing new potential for constructing multistrain pro- and symbiotics. Algorithms of such screening and constructing based on lectins-glycoconjugates interactions are developed. Proposed anaerobic (without oxidoreductase systems participating in oxidative stress) relatively high molecular mass synergistic symbiotic lectins (in contrast to low molecular mass acidic symbiotic effectors) are perspective as network multifunctional switching assistive recognition systems functioning in agreement to human protective systems (complement, lymphocytes, macrophages) in the absence of local availability of oxygen. Results support new technological prospects of the direct and indirect resulting protection involving human intestinal indigenous symbiotic (probiotic) lectin systems against surrounding pathogenic and/or relatively pathogenic exo- and endogenic microorganisms in biotopes of organism.